Predicting the optical response of plasmonic metamolecules using equivalent circuit models - Saad-Bin-Alam, M.; Huttunen, M.J.; K. L. Tsakmakidis; Dolgaleva, K. (2017 Photonics North, PN 2017, 2017)
Metamaterials provide functionalities that are not present in naturally occurring materials, including negative refraction, super-lenses or hyper-lens, cloaking, and ultraslow and stopped light [1-5]. Usually, both the electric permittivity and the magnetic permeability need to be controlled to realize metamaterials. © 2017 IEEE.
cited By 0